Production of leukotriene B4 by Paracoccidioides brasiliensis - Biondo, Guilherme Augusto; Dias-Melicio, Luciane Alarcao [UNESP]; Bordon-Graciani, Ana Paula; Kurokawa, Cilmery Suemi [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP] (Wiley-Blackwell, 2012)
Paracoccidioides brasiliensis is the agent of paracoccidioidomycosis, the most prevalent deep mycosis in Latin America. The production of eicosanoids during fungal infection has been associated with the biology of these microorganisms and modulation of host immune response. The aim of our study was to evaluate whether P. brasiliensis strains with high or low virulence produce leukotriene B4 (LTB4), using endogenous and/or exogenous sources of arachidonic acid (AA). Moreover, we assessed whether this fungus might use the same metabolic pathway, described for mammalian cells, that involves the lipoxygenase (LOX) enzyme. The association between the production of this eicosanoid and fungus survival and growth was also evaluated. Our results showed that P. brasiliensis, irrespective of its virulence, produces high levels of LTB4 using endogenous AA. In addition, in cultures treated with exogenous AA, LTB4 levels were significantly higher, showing that this fungus also uses exogenous sources of fatty acids. Treatment with MK886, which blocks the activity of lipoxygenase, by inhibiting five-lipoxygenase-activating protein (FLAP) or with nordihydroguaiaretic acid (NDGA), a non-selective lipoxygenase inhibitor, resulted in a significant reduction in LTB4 levels, indicating that the fungus produces this eicosanoid by using the LOX pathway or an enzyme with biochemically similar function. The significant reduction in viability detected in cultures treated with these inhibitors was, however, restored by adding exogenous LTB4, confirming the role of this eicosanoid in fungus survival. Moreover, the addition of LTB4 to cultures capable of producing LTs induces fungal growth. These results provide a foundation for additional studies on the contributions of LTB4 in P. brasiliensis virulence. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: Paracoccidioides brasiliensis; leukotriene B4; lipoxygenase; fungal survival